Behind the council agenda: The commission's impact on decisions - Susanne K. Schmidt (Max-Planck-Institut für Gesellschaftsforschung, 1997)
This paper contributes to the ongoing discussion about the scope for autonomous action of supranational organizations in the European Union, focussing on the European Commission. In the literature, the independence of the Commission is frequently questioned, while the relative autonomy of the European Court of Justice is less contentious. The Commission's power is largely related - and restricted - to its role as an agenda-setter. Particular emphasis is accorded to its agenda-setting powers as an avenue of influence. What has so far been seldom recognized is how the Commission can profit from its specific role in the supranational legal system. I present empirical evidence showing how the Commission can take advantage of the supremacy of European law, and force the Council to act. Thereby it manages to influence the course of European integration largely independently, benefitting from the greater autonomy of the European Court. – – Die Grenzen der Handlungsfähigkeit supranationaler Organisationen in der EU werden heftig debattiert. In der Literatur wird die Unabhängigkeit des Europäischen Gerichtshofs anders als die der Korrission kaur bezweifelt. Mit den Handlungsröglichkeiten der Korrission beschäftigt sich dieser Beitrag. Sie werden in den reisten Analysen rit ihrer Vorschlagsrecht verbunden. Dagegen wird zu wenig beachtet, in welcher Maße die Korrission von den ihr ir supranationalen Rechtssyster zugedachten Aufgaben profitieren kann. Anhand einiger Beispiele zeige ich, wie die Korrission ihre Rolle als Hüterin der Verträge dazu nutzen kann, den Ministerrat zur Handeln zu zwingen. Auf diese Weise verrag die Korrission die Europäische Integration weitgehend eigenständig zu beeinflussen. Dabei profitiert sie von der größeren Unabhängigkeit des Europäischen Gerichtshofs.+#
Keywords: 300